Hipoalbuminemia: Pengaruhnya pada Farmakokinetika Agen-Agen Anestesi - Mahmud; Wardhana, Ardyan Prima; Widyastuti, Yunita (Jurnal Komplikasi Anestesi, 2017)
Hypoalbuminemia is a condition in which the serum albumin contentration less than 3.5 mg / dL. Albumin serves as a binding protein and carrier of various substances including drugs. This manuscript discusses the effect of plasma albumin levels on pharmacokinetics changes of anesthetic agents. Inhalation and mostly intravenous anesthetic agents are lipophilic and highly protein binding. The albumin concentration is directly proportional to the blood/gas partition coefficient. For the intravenous agent, the unbound drug concentration gradient between plasma and tissue will be increased under conditions of hypoalbuminemia. The changes in volume distribution and elimination half-life occur, but unbound drug concentration in steady conditions does not depend on the amount of drug binding to proteins. Bolus administration of anesthetic agents generally does not require dose adjustment under hypoalbuminemia. It differs in continuous administration. There are few clinical studies of anesthetic agents in patients with hypoalbuminemia. Generally, clinical studies are conducted in patients with cirrhosis, which can be accompanied by hypoalbuminemia. One study was able to demonstrate a change in clinical effects seen in the administration of infusion propofol as well as repeated injections compared with bolus during induction.